Navigating the Digital Era: AI's Influence on Educational Quality Management - Adeoye, Moses Adeleke; Obi, Sabina Nwakaego; Sulaimon, Jamiu Temitope; Yusuf, Jamilla (STKIP Pesisir Selatan, 2025)
Artificial Intelligence (AI) has a major impact on the world of education, both positively and negatively. Positively, AI can increase the efficiency and personalization of learning. This technology enables adaptive learning systems that adjust materials and learning speeds according to student needs. Teachers are also helped by the existence of automatic evaluation systems, analysis of student learning data, and virtual assistants to answer student questions in real-time. In addition, AI can expand access to education through intelligent and interactive online platforms, reaching even remote areas. However, there are also challenges and negative impacts. Reliance on technology can reduce social interaction and the role of teachers as primary educators. Not all students or schools have access to adequate devices and internet connections, which can widen the educational gap. On the ethical side, AI raises concerns about data privacy and the potential for algorithmic bias in assessments or recommendations. This study explores the impact of Artificial Intelligence (AI) on education quality management. It highlights the challenges faced by traditional systems in a rapidly digitizing world and explores key AI technologies such as data analytics, personalized learning platforms, and administrative efficiency tools. The paper also discusses how AI can enhance existing quality management frameworks by encouraging continuous improvement models and promoting stakeholder engagement. It critically examines ethical considerations of AI integration, acknowledging potential bias and privacy concerns. It also discusses barriers to implementation such as resource constraints and resistance to change. It proposes recommendations for future policy development and responsible implementation of AI, including establishing guidelines for the ethical use of AI, prioritizing data privacy, and fostering a culture of continuous learning and adaptation. It emphasizes the need for a proactive approach to integrating AI into educational quality management.